NILAI TANGGUNG JAWAB DALAM NOVEL LASKAR PELANGI KARYA ANDREA HIRATA: TINJAUAN STRUKTURALISME GENETIK - Siti Rukiyah (LPPM STKIP PGRI Bandar Lampung, 2019)
This study discusses in depth about the moral values of responsibility in the novel Laskar Pelangi. Furthermore, the proposed related to the socio-cultural background of the authors in the creation of novel Laskar Pelangi effect on moral values. In addition, also discussed the author's view of the world related to the teachings of the value of responsibility. This research uses a qualitative approach with content analysis method. The results showed that the value of responsibility based on the novel structure consisting of man's relationship to himself, namely in terms of character and characterization. The characters are displayed Andrea Hirata bring the characters responsible for the thoughts, attitudes, and behavior. From a review of genetic structuralism, the value of responsibility based on social and cultural background, knowledge systems also influence the social and cultural life. Belitung people's livelihood systems are revealed also shape the character responsible. The author's world view of morals includes the value of self-existence, self-esteem, self-confidence, fear, longing, and responsibility.